POSITIVE POLITENESS STRATEGY USED BY MICHELLE OBAMA ON THE NPR (NATIONAL PUBLIC RADIO) YOUTUBE - Novia Sari, Aisyah Laily; Prasetyani, Nuning Yudhi (University of Darussalam Gontor, 2024)
This study, titled Positive Politeness Strategies Used by Michelle Obama on NPR’s YouTube, analyzes the positive politeness strategies employed by Michelle Obama in her interview with Juana Summers on NPR’s Michelle Obama Talks Parenting, Partnership, and Turning Your Rage Into Change, released on YouTube on November 15, 2022. Using Brown and Levinson's (1987) theory of positive politeness, this qualitative research identifies thirteen strategies, including intensifying interest, presupposing and asserting, attending to the interlocutor, seeking agreement, exaggerating interest or approval, presenting disagreement, asserting or presupposing shared beliefs, being optimistic, offering and promising, giving empathy and understanding, using identity markers, and joking. These strategies enable Michelle Obama to create a positive public image, build rapport with the host, and facilitate a meaningful dialogue. The study underscores the value of positive politeness in public communication to foster audience connection and engagement.